Rubber Seed Oil Properties, Authentication and Quality Assessment Using (Chloroform: Methanol) as Solvent - Yousif, Emad; Abdullah, Bashar; Ibraheem, Hanan; Salimon, Jumat; salih, Nadia (Al-Nahrain Journal of Science, 2013)
Physicochemical and instrumental characterization of rubber (Hevea brasiliensis (kunth. Muell.)) seed oil (RSO) were carried out for the purpose of quality assessment, identification, and authentication. Properties such as free fatty acid (FFA %), acid value, color, saponification value, iodine value, and unsaponifiable matter were determined. Fatty acid (FA) composition and TAG profiles were determined using gas chromatography (GC) and high performance liquid chromatography (HPLC), respectively. Structural features of RSO were also determined using FTIR, 1H NMR and 13C NMR spectroscopy. The natural form of RSO is highly acidic (acid value=17.43±0.06 mg KOH/g). The saturated FAs are palmitic (9.10±0.06) and stearic (12.63±0.01), and the main unsaturated FAs are oleic (25.31±0.13), linoleic (36.31±0.09), and linolenic (15.78±0.18). The oil can be classified as semidrying. Polyunsaturated TAGs of LnLnL and LnOO were the major TAGs found in RSO. FTIR, 1H NMR and 13C NMR analysis confirmed that RSO is composed mainly of TAG of saturated and unsaturated FA.